2017
DOI: 10.1111/epi.13632
|View full text |Cite
|
Sign up to set email alerts
|

Malformation risk of antiepileptic drug exposure during pregnancy in women with epilepsy: Results from a pregnancy registry in South India

Abstract: This dataset from South India confirms the increased risk of MCM with exposure to AEDs, particularly polytherapy. A dose-dependent increased risk was observed with valproate. The increased risk associated with clobazam monotherapy is an important signal that needs to be confirmed in a larger sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(91 citation statements)
references
References 13 publications
3
76
2
9
Order By: Relevance
“…In women with epilepsy, it is known that the risk of birth defects in general and orofacial clefts in their offspring is significantly elevated. Present results are in accordance with the literature data . It is important to note that the possible teratogenic effect of antiepileptic drugs in these cases must also be taken into consideration .…”
Section: Discussionsupporting
confidence: 91%
“…In women with epilepsy, it is known that the risk of birth defects in general and orofacial clefts in their offspring is significantly elevated. Present results are in accordance with the literature data . It is important to note that the possible teratogenic effect of antiepileptic drugs in these cases must also be taken into consideration .…”
Section: Discussionsupporting
confidence: 91%
“…It is now well demonstrated that exposure to some AEDs during pregnancy increases the risk of major congenital malformations in the offspring, such as neural tube defects and cleft palate, from two‐fold to three‐fold . The risk varies by AED: valproate is known to have the highest risk whereas lamotrigine may represent the safest AED during pregnancy .…”
Section: Introductionmentioning
confidence: 99%
“…1 It is now well demonstrated that exposure to some AEDs during pregnancy increases the risk of major congenital malformations in the offspring, such as neural tube defects and cleft palate, from two-fold to three-fold. [2][3][4][5] The risk varies by AED 6 : valproate is known to have the highest risk 2 whereas lamotrigine may represent the safest AED during pregnancy. 5 Furthermore, since the early 2000s, several studies have suggested a risk of neurodevelopmental problems in children exposed in utero to valproate 7 including delayed walking and talking or difficulty with language.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic and serious nature of some of the indications for which they are prescribed means that it is not always possible for women to discontinue their treatment in advance of and during pregnancy . For some time, there has been evidence that certain AEDs, when taken by women during their pregnancy, are associated with a two‐ to three‐fold increase in risk of major congenital malformations in the offspring . The risk varies by AED, with sodium valproate often reported as having the highest risk and lamotrigine and levetiracetam the lowest risk, although for many of the other newer AEDs, the number of exposures during pregnancy available for study is low.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] For some time, there has been evidence that certain AEDs, when taken by women during their pregnancy, are associated with a two-to three-fold increase in risk of major congenital malformations in the offspring. [14][15][16][17] The risk varies by AED, with sodium valproate often reported as having the highest risk 14 and lamotrigine and levetiracetam the lowest risk, 17 although for many of the other newer AEDs, the number of exposures during pregnancy available for study is low. In recent years, there has been a growing body of evidence of negative neurodevelopmental outcomes in children exposed to sodium valproate in utero.…”
mentioning
confidence: 99%